THE CORRELATION BETWEEN HEMODIALISA DURATION AND APPETITE TO PATIENTS WITH CHRONIC KIDNEY FAILURE (CKD) AT PUBLIC HOSPITAL OF dr. SOEKARDJO TASIKMALAYA CITY - Bayu Brahmantia; Mila Herlina; Yuyun Solihatin; Hana Ariyani; Heri Budiawan; Asep Mukhsin (Suluh Adiluhung Publisher (SAPub), 2024)
Chronic Kidney Failure (CKD) is a condition where the kidneys do not function properly, occurring for or more than 3 months. CKD patients require prolonged renal replacement therapy to survive, one of which is hemodialysis. The problem often faced by patients undergoing hemodialysis is decreased appetite. The aim of this research is to determine the relationship between the duration of hemodialysis and appetite in CKD sufferers at Public Hospital of dr. Soekardjo, Tasikmalaya City. The method used is quantitative correlational with a cross sectional approach. The population in this study were all hemodialysis patients at Public Hospital of dr. Soekardjo Tasikmalaya City numbered 97 people using total sampling techniques. Data collection on appetite was obtained using the SNAQ (Simplified Nutritional Appetite Questionnaire) questionnaire, duration of hemodialysis using a characteristic data collection sheet and analyzed using the chi square test. The results showed that most of the respondents' hemodialysis duration was ≤1 year (28.9%) and most of the respondents' appetite was poor (50.5%). The results of statistical tests on the correlation between duration of hemodialysis and appetite in chronic kidney failure sufferers obtained p value = 0.003 < 0.05. So, it can be concluded that there is a correlation between hemodialysis duration and appetite to patients CKD at Public Hospital of dr. Soekardjo, Tasikmalaya City. It is recommended that nurses provide education to families in dealing with appetite complaints by providing attractive foods according to dietary recommendations.